2009
DOI: 10.1039/b907903c
|View full text |Cite
|
Sign up to set email alerts
|

An ellipsometry study of silica nanoparticle layers at the water surface

Abstract: We have studied silica nanoparticle layers spread at the air-water interface. The surface pressure of the layers has been determined in a Langmuir trough via two orthogonal Wilhelmy plates. We observed significant differences in surface pressure according to the preparation protocol: layers spread then compressed or layers obtained after successive spreading steps. We also studied the two types of layers by multiple angle of incidence ellipsometry. We introduce a two-layer model which enables us to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
46
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 44 publications
7
46
1
Order By: Relevance
“…The contact angle increases with an increasing degree of silanization. It has been shown recently that ellipsometry allows in situ measurements of adsorbed particles [13] and leads to similar values of θ to those in ref. 8.…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…The contact angle increases with an increasing degree of silanization. It has been shown recently that ellipsometry allows in situ measurements of adsorbed particles [13] and leads to similar values of θ to those in ref. 8.…”
Section: Introductionsupporting
confidence: 55%
“…Although the layer properties depend upon the preparation method, it has been shown that the layers deposited on a clean water surface without being subsequently compressed are similar to the layers adsorbed from the particle dispersions used to generate the foams [13]. In this paper, we extend the previous study of deposited layers of the particles that give the most stable foams (θ ~ 90°) [16], investigating particles exhibiting both larger and smaller contact angles.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Furthermore, fluorescence loss induced by photobleaching and fluorescence recovery after photobleaching on the same system revealed that the lateral diffusion of these assemblies is 4 orders of magnitude slower than its bulk counterpart. 36 Second harmonic generation, 37 surface plasmon resonance 38 and ellipsometry 39 have also been shown as a characterization method for NPs at the LLI. More recently, freezefracture shadow-casting cryo SEM has been performed with single-particle resolution of these assemblies.…”
mentioning
confidence: 99%
“…However, the literature provides many examples of layers buckling before this zero tension state is reached. For example, interfaces coated with spherical [11] and ellipsoidal [12] colloidal particles buckle upon compression whilst the interfacial tension is still a significant fraction of its value before coating. Although commonly observed, the buckling of layers with finite shear modulus has yet to be fully understood from a theoretical point of view.…”
mentioning
confidence: 99%